Quo vadis iurisprudentia? Denaturation in the outsourcing in the Peruvian legal system - Puntriano Rosas, César (2019)
In the article, the author analyzes the denaturing in labour outsourcing using relevant case law. Also, the author addresses the advantages of outsourcing and its negative impact in workers’ conditions. The author proposes the realization of a caseby-case analysis, in order to analyze whether the denaturing of the outsourcing occurs in each specific case and, thus, avoid excesses.